Identification of a novel anoikis signalling pathway using the fungal virulence factor gliotoxin - Haun, Florian; Habicht, Jüri (Nature Communications, 2018)
Gliotoxin (GT), produced by the pulmonary pathogen A. fumigatus, induces detachment-induced apoptosis (anoikis) of lung epithelial cells and likely promotes invasion. Here, the authors show that GT covalently modifies integrins at the RGD binding site followed by activation of RhoA-ROCK-MKK4/7-JNK signalling leading to Bim-mediated anoikis.
Gesehen am 22.10.2019